2018
DOI: 10.1097/md.0000000000011578
|View full text |Cite
|
Sign up to set email alerts
|

The effects of statin therapy on mortality in patients with sepsis

Abstract: Background:Much controversy persists regarding the role of statins therapy in patients with sepsis. This systematic review and meta-analysis of randomized trials aimed to evaluate the clinical efficacy of statin therapy on mortality from sepsis.Methods:We comprehensively searched PubMed, Embase, and Cochrane controlled trials register for relevant clinical studies. Randomized controlled trials reporting the effect of statin therapy on mortality in septic patients were included. Pooled risk estimates were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
3
20
1
1
Order By: Relevance
“…[55][56][57][58][59][60][61] Nevertheless, a recent meta-analysis of seven randomised clinical trials showed no benefit of statin therapy on mortality in patients with sepsis compared with placebo. 62 Our findings, on the other hand, demonstrated a clear mortality benefit with statin therapy independent of other covariates and warrant further studies to validate these results.…”
Section: Open Accesssupporting
confidence: 62%
“…[55][56][57][58][59][60][61] Nevertheless, a recent meta-analysis of seven randomised clinical trials showed no benefit of statin therapy on mortality in patients with sepsis compared with placebo. 62 Our findings, on the other hand, demonstrated a clear mortality benefit with statin therapy independent of other covariates and warrant further studies to validate these results.…”
Section: Open Accesssupporting
confidence: 62%
“…Moreover, a randomized trial of the effect of atorvastatin in patients with severe sepsis indicated that prior statin users had lower 28-day mortality than placebo users [33]. However, a meta-analysis of nine randomized trial studies concluded that statin therapy had no effect on mortality outcomes in patients with sepsis compared with placebo users [34]. In a previous double-blind investigation, treatment of hypercholesterolemia with lovastatin did not cause psychological distress or substantially alter cognitive function [35].…”
Section: Discussionmentioning
confidence: 99%
“…Simvastatin had been proved to be effective in hemodynamic stabilization, improved responses to beta-adrenergic vasopressin drugs, increasing blood pressure, and decreased adhesion of polynuclear cells to the previously activated endothelium in animal study. [10,11,16] Although a meta-analysis based on 9 prospective randomized trials had concluded that statin could not improve mortality in septic patients compared with placebo-controls, [17] a meta-analysis of 27 observational studies concluded that statin treatment could reduce mortality by 35% in patients of sepsis. [14] In this current cohort study, we concluded that the use of statins after post-sepsis discharge improved the long-term prognosis of patients who had survived sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…It is described as a higher health awareness and healthier lifestyle in patients of statin-users, compared with nonstatin users. [14,17,29] According to this theory, statin-users are more likely to seek out preventive healthcare services, such as screening tests and vaccinations. [29,30] However, it is quite difficult to measure the factors involving lifestyle, prevention behavior toward disease, and compliance of drugs in observational studies.…”
Section: Discussionmentioning
confidence: 99%